Relationship Between International Trade and Foreign Direct Investment: The cross impact in china (1991-2016) - عاقل سماح; رولا اسماعيل (Latakia University Journal - Economic and Legal Sciences Series, 2024)
China has sought to attract foreign direct investment flows to take advantage of the accompanying advantages, such as technology transfer, facilitating access to international markets, improving productivity and the competitiveness of local institutions, and China has been able to achieve an advanced level in the field of foreign direct investment, as it is the first developing country that is most attractive to foreign direct investment, and the second globally after the United States of America in 2012. This paper investigates the relationship between foreign direct investment (FDI) and the foreign trade of China during the period (1994-2016). It firstly encompasses a theoretical discussion of the mutual impact of FDI and foreign trade, and then provides an analytical study of the variables, which included the development of foreign direct investment and the commodity structure of Chinese exports and imports during the studied period. The study concludes that there is no relationship between (FDI) and foreign trade in China, the results can be explained by the fact that the incoming foreign direct investment into China was mostly directed to non-export sectors.